Impact of Basset force on threshold values of particle drag coefficient and density parameter in standing sinusoidal wave - D. A. Gubaidullin; P. P. Osipov; A. N. Zakirov (Известия высших учебных заведений: Проблемы энергетики)
The inclusion drift in a standing sinusoidal fluid-velocity wave at various Reynolds and Strouhal numbers under the action of the viscous force, the virtual mass force, the buoyancy force and Basset force has been investigated. For a given inclusion density, as the standing wave frequency increases, its threshold value, above which the direction of the wave force reverses, is attained sooner or later. For various Reynolds and Strouhal numbers (with and without Basset force), the dependences of the squared threshold drag coefficient on the inclusion density number have been found. These dependences show that with increasing Reynolds and Strouhal numbers the threshold value of the squared drag coefficient decreases markedly. Basset force influence on a threshold value has been investigated. It has been shown, that Basset force influence most on threshold values of low-density inclusions.